2010
DOI: 10.1007/s10551-010-0513-2
|View full text |Cite
|
Sign up to set email alerts
|

Risky Rescues and the Duty to Blow the Whistle

Abstract: duty, legislation, obligation, right, whistleblowing, whistleblowing policies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 35 publications
(51 reference statements)
1
22
0
2
Order By: Relevance
“…Bl.a. har Vandekerckhove (2006) undersøgt, hvordan begrundelserne for at indføre whistleblower-ordninger påvirker deres endelige udformning og diskuteret implikationerne af, hvordan whistleblowing kan tolkes som både rettighed og pligt i forbindelse med disse (Vandekerckhove & Tsahuridu 2010). Andre studier belyser de praktiske og juridiske aspekter af den konkrete implementering af whistleblower-ordninger (Lewis 2001(Lewis , 2002(Lewis , 2006Lind 2011; Søndberg & Winther 2011; Johnsen 2011: 1) samt ledelsens handlerum i denne nye kontekst (Smith & Oseth 1993).…”
Section: Eksisterende Forskningunclassified
“…Bl.a. har Vandekerckhove (2006) undersøgt, hvordan begrundelserne for at indføre whistleblower-ordninger påvirker deres endelige udformning og diskuteret implikationerne af, hvordan whistleblowing kan tolkes som både rettighed og pligt i forbindelse med disse (Vandekerckhove & Tsahuridu 2010). Andre studier belyser de praktiske og juridiske aspekter af den konkrete implementering af whistleblower-ordninger (Lewis 2001(Lewis , 2002(Lewis , 2006Lind 2011; Søndberg & Winther 2011; Johnsen 2011: 1) samt ledelsens handlerum i denne nye kontekst (Smith & Oseth 1993).…”
Section: Eksisterende Forskningunclassified
“…For example, Vandekerckhove and Commers (2004) use the descriptive research to argue how the debate around loyalty was a mistaken one. Also, descriptive ethics research is used to provide complexity to normative prima facie positions on whether whistleblowing is a right or a duty, and what the implications are for implementing such policies (Tsahuridu & Vandekerckhove, 2008;Vandekerckhove & Tsahuridu, 2010).…”
Section: The Impact Of the Situationmentioning
confidence: 99%
“…Hassink et al (2007) found that a substantial number of internal whistleblowing policies used wording which suggested that raising a concern is compulsory and employees might be held accountable for failing to do doing so. Tsahuridu and Vandekerckhove (2008) and Vandekerckhove and Tsahuridu (2010) have further theorised on this.…”
Section: Section 2: Frameworkmentioning
confidence: 99%